Maria paints the hills - Mora, Pat.; Hesch, Maria, 1909-1994 (Santa Fe, N.M. : Museum of New Mexico Press, 2002)
Maria and her mother experience daily life in Santa Fe, New Mexico.
4-8.
Keywords: Mexican Americans -- Juvenile fiction; Mexican Americans -- Fiction; Mothers and daughters -- Fiction; Families -- New Mexico -- Fiction; New Mexico -- Fiction